Enhanced Production of Fibrinolytic Enzyme from Pseudomonas aeruginosa by Optimization Media Components - Bilal Jasim; Entesar Ali (Journal of Applied Sciences and Nanotechnology, 2021)
Fibrinolytic enzyme is factor that lysis fibrin clots. This fibrinolytic factor has prospective use to treat cardiovascular diseases, such as stroke and heart attack. Cardiovascular diseases attracted worldwide attention for their elevation morbidity and mortality. Expensive cost and fatally undesired side effects associated with the available fibrinolytic agents to treat these diseases stimulated the researchers to investigate potentially better agents for curative applications. In the current investigation, fibrinolytic enzyme production from Pseudomonas aeruginosa isolated from injuries of wounds and burns patients. Parameters for the promoted production of the enzyme under minimal production media were optimized. It comprised carbon source (glucose), Nitrogen source (Yeast extract), Fibrinogen concentration (0.5 %), inoculum size (1 %), temperature (37°C), and PH (7). Enhanced fibrinolytic enzyme activity (136.2 IU/ml) was obtained after optimization Medium Components compared with that obtained with the minimal medium (60.2 IU/ml) which is 2.2 times higher than the same under non optimized production conditions. Media optimization researches for enhancement of fibrinolytic enzyme production from Pseudomonas aeruginosa in Iraq has not been performed so far. This may be the first study to optimization media for the production of fibrinolytic enzyme from Pseudomonas aeruginosa. The importance of this study lies in the enhancing the production of the fibrinolytic enzyme with high activity using these bacteria.